Odnos koncentracije homocisteina i mokraćne kiseline kod bosanskohercegovačkih dijabetičara s akutnim infarktom miokarda - Marković Boras, Marijana; Čaušević, Adlija; Ćurlin, Marina (Journal of Medical Biochemistry, 2020)
BackgroundCoronary artery disease as a consequence of atherosclerosis is the most common cause of morbidity and mortality in type 2 Diabetes Mellitus (DM) patients. Homocysteine (HCY), as one of the risk factors, and uric acid (UA) as the most common antioxidant in serum have their roles in the processes of inflammation and atherogenesis, which underlie the pathogenesis of acute myocardial infarction (AMI). The effect of HCY in cardiovascular disease is thought to manifest primarily through oxidative damage, impling potential correlation between the HCY level and antioxidant status. Since the data related to diagnostic significance of both HCY and UA in diabetic patients with AMI are conflicting, and so far not reported in Bosnian patients, the aim of this research was to examine the association of HCY and UA levels with glomerular filtration rate (eGFR) and explore the pathophysiological significance of these data in Bosnian diabetic patients with AMI.MethodsThis prospective research included 52 DM type 2 patients diagnosed with AMI. Blood samples were taken on admission, and used for biochemical analysis. Results of the biochemical analyses were statistically analyzed.ResultsElevated HCY and UA levels were observed in diabetic patients. Females have higher HCY compared to males. Positive correlation was revealed between HCY and UA and was confirmed with different HCY levels in subgroups with different UA level. Negative correlation was observed between UA and HbA1c, as well as between both HCY and UA with eGFR.ConclusionsThese results contribute to clarification of the biochemical mechanisms characteristic in AMI patients with DM. According to these results, we believe that joint measurement of HCY and UA could enable a better assessment of the prognosis for this group of patients.  This kind of assessment, as well as regression analysis can identify high-risk patients at an earlier stage, when appropriate interventions can influence a better outcome in such patients.